Breakthrough cases of Omicron and Delta variants of SARS-CoV-2 during the fifth wave in Pakistan - Jamal, Zunera; Haider, Murtaza; Ikram, Aamer; Salman, Muhammad; Rana, Muhammad Suleman; Rehman, Zaira; Haider, Syed Adnan; Ammar, Muhammad; Nisar, Nadia; Umair, Massab (Frontiers in Public Health, 2022)
COVID-19 pandemic has severely affected Pakistan with 1,557,134 cases as of August 4, 2022. However, the data regarding breakthrough infections in Pakistan is scant. Hence, the objective was to analyze SARS-CoV-2 breakthrough infections with respect to vaccines and variants during the fifth wave in Pakistan. Therefore, the Department of Virology (NIH, Pakistan) genotyped 2,467 randomly selected individuals between November 2021 and February 2022 using the SNPsig® SARS-CoV-2 (EscapePLEX) kit (PrimerDesign, UK). P681R and K417N mutations were used to distinguish delta and omicron. Data on the patient's age, gender, date of collection, variant, and vaccination status were analyzed using Statistical Package for Social Sciences (SPSS) software. Among 2,467 genotyped samples, Omicron was detected in 58.6% (n = 1445), Delta in 40.4% (n = 998) and undetermined/wildtype variant in 24 samples. The vaccination status of omicron-positive patients showed (49.7%; n = 718/1445) and Delta-positive patients (39.67%; n = 396/998) to be fully vaccinated. Of note, a high percentage 85% of breakthrough cases (n = 947) were identified among fully vaccinated individuals (n = 1114). Among them, 85.9% (n = 617/718) belonged to omicron and 83.3% (n = 330/396) to delta. Moreover, 76.7% (n = 855) of vaccinated individuals (n = 1114) received Sinopharm (n = 432) and Sinovac (n = 423) vaccines. The majority of breakthrough subjects who contracted Omicron were vaccinated with Sinopharm (93.0%, n = 256) and delta with Cansino (100%, n = 44). Individuals vaccinated with Sinovac showed the most frequent breakthrough cases for both Omicron and Delta variant between the 4th and 6th months (n = 278) after primary vaccination as compared to the 7th to 9th months (n = 24) category. While in case of Sinopharm, maximum breakthrough cases occurred between 7th to 9th months (n = 234) as compared to the 4th to 6th months (n = 120) after primary vaccination. Omicron and Delta breakthrough cases in men (n = 364 and 193) are more frequently seen than women (n = 253 and 138) respectively and breakthrough majority cases (n = 392) occurred in individuals aged 18–33 years. Breakthrough cases limiting monitoring in Pakistan impose a substantial constraint on policymakers' ability to take timely effective decisions. Since the current study consists of only a 2,467-genotyped sample, comprehensive data should be analyzed.